Gold nanoparticles/ionophore modified screen printed electrode for detection of Pb(II) and Hg(II) - Abdullah, Samir Diler (2016)
Contamination of water by toxic metal ions, such as lead and mercury, can lead to serious environmental and health problems. Therefore, monitoring toxic metal ions in natural water supplies requires creation of miniature, low-cost, and highly sensitive detectors that are capable of specifically identifying target substances. In the present work, gold nanoparticles (AuNPs), prepared by citrate reduction method, were combined with ionophore for use as a modifier for disposable screen printed electrodes (SPE) for the detection of Pb(II) and Hg(II) ions. The AuNPs was characterized by different spectroscopic techniques, and the application of AuNPs on surface of the electrode increases the sensitivity of this electrode. due to their excellent electrical conductivity and strong adsorption ability. In addition, Pb ionophore and Hg ionophore are utilized for its excellent selectivity towards Pb(II) and Hg(II) ions. The screen printed electrode was modified by casting a mixture of AuNPs and ionophore onto the working electrode’s surface, Then, (AuNPs/ionophore/SPE) electrode was applied for Hg(II) and Pb(II) detection. The electrochemical studies, using linear sweep voltammetry were performed with AuNPs/ionophore/SPE, gave a high response towards target ions under optimized parametersof some analytical parameters. A concentration study of lead with AuNPs/lead ionophore/SPE gave linear calibrations and a detection limit of 0.0823 mg L-1 was achieved by applying a deposition potential of -1.2 V and a deposition time of 240 s. The electrode showed very good recovery, thus indicating the accuracy of the method. Meanwhile, a concentration study of mercury with AuNPs/mercury ionophore/SPE gave a linear calibration of R2 = 0.99 and a detection limit of 1.06 μg. L-1 was achieved by applying a deposition potential of -1.2 V and a deposition time of 240 s. Validation of the method, with inductively coupled plasma-mass spectroscopy (ICP-MS), showed a very good correlation. Furthermore, the selectivity effect of ionophore towards the target ions, studied in the presence of other competitive ions in water samples, such as SO3 2-, SO4 2-, Fe3+, Mg2+, Cu2+ and Cd2+, gave an excellent selectivity.